2020
DOI: 10.48550/arxiv.2007.12260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of integral equations for the Maxwell transmission problem with general permittivities

Abstract: Two recently derived integral equations for the Maxwell transmission problem are compared through numerical tests on simply connected axially symmetric domains for non-magnetic materials. The winning integral equation turns out to be entirely free from false eigenwavenumbers for any passive materials, also for purely negative permittivity ratios and in the static limit, as well as free from false essential spectrum on non-smooth surfaces. It also appears to be numerically competitive to all other available int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our description of σ ess (K , H 1/2 (∂ )) ∩ R + is particularly simple for convex polyhedra, since one only needs to consider the double layer potential of − S 2 + 1/4 to compute this interval. Note that spectral parameters λ ∈ (0, 1/2) correspond to permittivities satisfying < −1; in [18,Sect. 8], it is suggested that < −1 is likely to be a necessary condition for the existence of surface plasmon waves on ∂ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our description of σ ess (K , H 1/2 (∂ )) ∩ R + is particularly simple for convex polyhedra, since one only needs to consider the double layer potential of − S 2 + 1/4 to compute this interval. Note that spectral parameters λ ∈ (0, 1/2) correspond to permittivities satisfying < −1; in [18,Sect. 8], it is suggested that < −1 is likely to be a necessary condition for the existence of surface plasmon waves on ∂ .…”
Section: Resultsmentioning
confidence: 99%
“…If is Lipschitz and U is assumed to be of finite energy, then any plasmonic eigenvalue must satisfy that < 0, since Green's formula implies that R 3 \ |∇U | 2 dx = − |∇U | 2 dx. Plasmonic problems, where Re < 0, appear as quasi-static approximations of electrodynamical problems where the scatterer is much smaller than the wavelength of the scattered electromagnetic wave, see [1] and [18,Sect. 8].…”
Section: Introductionmentioning
confidence: 99%